Studi Gaya Desain Eklektik pada Interior Sagoo Kitchen di Bandung - Lisa Levina Jonatan; Stella Sondang (JURNAL RUPA, 2020)
In the current global culture continues to run with the concept of modernism that form follows function and formalism, there are some people who choose a lifestyle that is the opposite of postmodernism. Meaning of postmodernism is so diverse that the key concepts necessary to identify, one eclecticism. Eclecticism concept is translated into the term double-coding or double meanings (both directions) where the realization of aesthetic language idioms associated with the new aesthetic.The approach is made to the object of study, Sagoo Restaurant in analyzing the meaning of philosophy and the visual design of interior space.